Pengolahan Limbah Tahu Menjadi Biogas Sebagai Inovasi Guna Mengatasi Krisis Energi - Rindiani, Friska; ., Sudarti; ., Yushardi (CV. ITTC INDONESIA, 2023)
For most Indonesian people, tofu is a processed soybean-based food that is very popular among Indonesian people. Apart from being highly nutritious, tofu is also cheap and easy to make. The price is affordable for the general public and the taste is delicious. At the processing stage, the tofu industry produces both solid and liquid waste. The process of sifting and grouping solid waste produces waste which is mostly sold by experts and processed into animal feed, tempeh gembus which is made from tofu dregs, and leftover tofu flour which is used as a basic ingredient for making bread and baked goods. Meanwhile, a lot of liquid waste is produced during the process of washing tofu, boiling tofu, pressing tofu, and the process of forming tofu. Ecological benefits will be reduced if tofu liquid waste is directly disposed of into waters due to the high content of organic matter, BOD and COD. Therefore, the industry realizes that waste processing is necessary to reduce the current risk of pollution. Handling of tofu waste must continue to be carried out and monitored properly. Indonesia has the ability to create normal abundance in large quantities to channel elective energy. Therefore, the use of fuel sources requires substitute materials that are not harmful to the ecosystem and do not run out. Biogas is an environmentally friendly power plant that has a lot of development potential.